Unlimited and abundant labor supply: Econometric and other evidence in Philippine industry - Gerardo P. Sicat (University of the Philippines, School of Economics (UPSE), 2008)
The paper examines the Philippine labor market by fitting a labor supply equation using detailed firm data from the survey of manufactures. The Philippines continues to have high rates of unemployment and underemployment amidst a continuously rising labor supply. The results of the econometric effort confirm the description of the economy as falling within the zone of abundant labor supply at best if not within in the unlimited zone of labor supply. Segregating the different sizes of firms as individual characteristics does not change the basic econometric finding. The study further incorporates the effects of specific industry groupings, of which some were at the 3-digit level of aggregation. Taking account of specific industry characteristics brings out some unique findings. Labor intensive export industries and some wage goods industries organized under large firms tend to be sensitive to movements in the wage rate. But these industry groups are the exception rather than the rule and the values of the statistically significant aggregate wage response coefficients are very low values and almost close to zero. The paper further analyzes the wage differentials among major occupational groups and the nature of labor supply among professionals and technicians that require the passing of state administered board examinations. In general, both types of analysis provide additional confirmation of the excess labor supply at the level of the educated work force.
Keywords: 330; Labor market; Supply of labor; Philippine labor market; Philippine economy; Employment; Wage income; Occupational wage differentials; Arbeitsangebot; Industrie; Philippinen